Pendidikan Karakter Berbasis Budaya Lokal di Kampung Adat Cireundeu - Agustiana, Agustiana; Rahayu, Fuzi Astuti; Rahmatullah, M. Rizki; Nurfadilah, Syifa; Suherman, Ade (UNIVERSITAS SERAMBI MEKKAH, 2025)
Local culture-based character education in its implementation in traditional villages has a very strategic role in maintaining local wisdom values ​​while building national identity. This review aims to describe the implementation of local culture-based character education in daily life in the Cireundeu Traditional Village, Cimahi City, West Java. Through a qualitative descriptive approach, this research found that character education in the Cireundeu Traditional Village is based on the principles of simple living, respecting nature, and upholding the values ​​of mutual cooperation and togetherness that indigenous peoples always practice. These values ​​are then internalized through traditional practices, religious rituals, and social interactions of the traditional community and also in their implementation in the daily life of the traditional community of Cireundeu Village. In writing this journal, the focus is on research into the implementation of character education in the Cireundeu Traditional Village community through its local culture which still maintains and maintains the existence of traditions passed down from ancestors amidst the challenges of increasingly advanced globalization.